A feed-forward loop between lncARSR and YAP activity promotes expansion of renal tumour-initiating cells - Le Qu (Nature Portfolio, 2016)
Renal tumour-initiating cells (T-ICs) contribute to tumour initiation and progression. Here, the authors show that lncARSR regulates TICs by blocking LATS1-induced YAP phosphorylation facilitating YAP nuclear translocation, which promotes lncARSR transcription, thus forming a feed-forward circuit to promote TIC expansion.